(D)over-barN interaction from meson-exchange and quark-gluon dynamics - Haidenbauer, J.; Krein, G.; Meissner, U.-G.; Sibirtsev, A. (Springer, 2007)
We investigate the (D) over barN interaction at low energies using a meson exchange model supplemented with a short-distance contribution from one-gluon exchange. The model is developed in close analogy to the meson-exchange KN interaction of the Julich group utilizing SU(4) symmetry constraints. The main ingredients of the interaction are provided by vector meson (rho, omega) exchange and higher-order box diagrams involving (D) over bar *N , (D) over bar Delta, and (D) over bar*Delta intermediate states. The short-range part is assumed to receive additional contributions from genuine quark-gluon processes. The predicted cross-sections for (D) over barN for excess energies up to 150MeV are of the same order of magnitude as those for KN but with average values of around 20mb, roughly a factor two larger than for the latter system. It is found that the omega-exchange plays a very important role. Its interference pattern with the rho-exchange, which is basically fixed by the assumed SU(4) symmetry, clearly determines the qualitative features of the (D) over barN interaction - very similiar to what happens also for the KN system.